2013
DOI: 10.1007/s00436-013-3336-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel serine/threonine protein phosphatase type 5 from second-generation merozoite of Eimeria tenella is associated with diclazuril-induced apoptosis

Abstract: Screening the anticoccidial drug targets is very important for developing novel drugs and revealing the molecular basis of drug resistance in coccidia. Due to high effectivity and safety, diclazuril was used widely in the poultry industry. To assess the roles of the serine/threonine protein phosphatase type 5 of second-generation merozoites in Eimeria tenella (EtPP5) in the anticoccidial activity of diclazuril against chicken coccidiosis, EtPP5 was cloned using reverse transcriptase polymerase chain reaction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…In mammals, PP5 regulates intracellular biological activities as diverse as cellular proliferation, differentiation, migration, survival and death, and DNA damage repair [8]. A recent study revealed that PP5 has an important role in the signaling mechanism associated with the diclazuril-induced merozoite apoptosis in Eimeria tenella [9]. To date, our knowledge of insect PP5 is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, PP5 regulates intracellular biological activities as diverse as cellular proliferation, differentiation, migration, survival and death, and DNA damage repair [8]. A recent study revealed that PP5 has an important role in the signaling mechanism associated with the diclazuril-induced merozoite apoptosis in Eimeria tenella [9]. To date, our knowledge of insect PP5 is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that mammalian systems lack the protochlorophyllidae related diclazuril/herbicide binding region results in a very high therapeutic index for diclazuril and related agents. In addition, diclazuril is shown to down-regulate expression of serine/threonine protein phosphatase (EtRACK) in second-generation merozoite of Eimeria tenella to induce apoptosis [31]. EtRACK has about 98% homology with Toxoplasma that demonstrates a possible mechanism of action for diclazuril.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, diclazuril binds the chloroplast epitopes to interact with the D1 protein of the photosynthetic reaction hub of Toxoplasma organelles, without any harmful effect on the host cells. Additionally, diclazuril can downregulate expression of serine/threonine protein phosphatase (EtRACK) in merozoites of Eimeria tenella chicken coccidiosis which results in apoptosis [46]. EtRACK has about 98% homology with Toxoplasma organisms which demonstrates a predicted mechanism of action for diclazuril against toxoplasmosis.…”
Section: Discussionmentioning
confidence: 99%